(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This study explores the intricate dynamics of translating stories between Uzbek and English, with a focus on the interplay between language and culture. The research delves into the linguistic and cultural features that characterize the translation process, aiming to provide insights into the challenges and strategies employed by translators. Through a comparative analysis of translated stories, the study examines how linguistic nuances, literary styles, and cultural references are navigated to create a narrative that resonates authentically with both the source and target audiences. The investigation addresses the adaptation of grammar, syntax, and vocabulary in the translation, shedding light on the choices made by translators to convey the intended meaning while respecting the linguistic peculiarities of each language. Cultural references and contextual elements are scrutinized to assess how translators manage the preservation of historical and social contexts, ensuring a nuanced and culturally sensitive narrative. The study also explores the impact of translation on the reader experience in terms of cultural authenticity and linguistic fluency. It aims to uncover patterns and trends in translation approaches, contributing valuable insights to the field of translation studies. Additionally, the research considers educational applications, offering recommendations to enhance translation practices in language and translation courses. By addressing these aspects, this study contributes to a deeper understanding of the complexities involved in translating stories between Uzbek and English. It emphasizes the role of translated literature in promoting cross-cultural understanding and lays the groundwork for further advancements in translation theory and practice.